Absent Relationship between the Coil-Embolization Ratio in Small Aneurysms Treated with a Single Detachable Coil and Outcomes - Goddard, James K.; Moran, Christopher J.; Cross, DeWitte T.; Derdeyn, Colin P. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Although attenuated coil packing of intracranial aneurysms is an important goal of endovascular embolization, because of their small size, some aneurysms can only be treated with a single embolization coil. We retrospectively analyzed small aneurysms treated with a single Guglielmi detachable coil (GDC) to determine whether the coil-embolization ratio (CER) is predictive of embolization stability.METHODS: The CER was determined for 25 small (<7-mm diameter) intracranial aneurysms, each treated with a single embolization coil. The largest aneurysm dimension, estimated by comparison to anatomic landmarks, was used for volume calculation based on a spherical model. Coil volumes were according to manufacturer specifications. CER was calculated by the formula (coil volume/aneurysm volume) × 100%. Embolization stability was assessed by angiographic follow-up.RESULTS: The average CER for all aneurysms was 8.2% (SD, 6.5%; range, 0.6%–21.1%). Twelve percent of the aneurysms had a CER >20%. Follow-up angiographic assessment was conducted at an average of 30.8 months after initial treatment. Eighty-four percent of the aneurysms were obliterated. One large (6 × 10 mm) and 3 small (<1 mm) recurrences were identified. The average CER for unchanged aneurysms was 8.0% (SD, 5.9%) and for the recurrent aneurysms was 8.8% (SD, 8.7%), which was not statistically significant.CONCLUSION: Small aneurysms treated with a single coil achieved satisfactory stability despite having a low average packing attenuation. CER was not predictive of recurrence in small intracranial aneurysms treated with a single detachable coil.